Evaluación de niveles de energía digestible en dos sistemas de alimentación en la respuesta productiva y reproductiva de cuyes (Cavia porcellus) - Sarria Bardales, José Antonio (2020)
The aim of this study was to evaluate diets with two levels of digestible energy (2.7 and 2.9 Mcal of ED/kg) and two feeding systems (with or without the inclusion of green forage) in female breeding guinea pigs, evaluating the response in productive and reproductive parameters (weight gain, food intake, litter size, fertility rate, births, abortions, mortality and birth and weaning weights), as well as the economic response. The study was conducted with 60 second-parity females of 1274 g of mean bodyweight and 12 improved male guinea pigs from the Cieneguilla Guinea Pig Farm of the La Molina Agrarian University, Lima, Peru. The study lasted for 18 weeks between May and October 2010. A 2x2 factorial statistical design was used with four treatments and three repetitions per treatment: T1 and T2 with diets of 2.7 Mcal of ED/kg with and without inclusion of green forage, respectively, and T3 and T4 with diets of 2.9 Mcal of ED/kg with and without inclusion of green forage, respectively. No significant differences were found between treatments in most of the indicators; however, mothers fed under forage inclusion systems lost weight at weaning (-47.6 g), while diets with the 2.9 Mcal energy level of ED/kg produced greater birth weight (p<0.05). The lowest cost per weaned offspring was obtained under the feed system including forage (S/. 5.00 vs. S/. 5.60).